ChemInform Abstract: P‐Arylation: Arynes to Aryl‐Phosphonates, ‐Phosphinates, and ‐Phosphine Oxides. Issue 35 (8th August 2013) - Dhokale, Ranjeet A.; Mhaske, Santosh B.
Abstract The reaction proceeds under metal‐free conditions and is efficient, regioselective, and general.